2016
DOI: 10.4491/eer.2015.120
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of leaf characteristics and wettability in retaining air particulate matter from tropical plant species

Abstract: In most African urban areas, Particulate Matters (PM) concentration exceeds by far the WHO limits. In these areas, plants can play a key role in removing particles. In this study, we evaluated three ornamental species (Jatropha interrigima, Ficus benjamina, Barleria prionitis) used in Abidjan (Ivory Coast). Leaf-encapsulated saturation isothermal remnant magnetisation (SIRM) were measured and the relationship between PM captured and leaf wettability were done. The sampling were performed at roadsides and Parks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
1
11
0
1
Order By: Relevance
“…3). It is to be noted that broad hairy leaf with a slight sticky wax can retain fine particulates for a long time [2,30,36]. A similar observation was seen in AM and all the species of Ficus due to waxy-glabrous leaf.…”
Section: Dac and Aptisupporting
confidence: 65%
See 1 more Smart Citation
“…3). It is to be noted that broad hairy leaf with a slight sticky wax can retain fine particulates for a long time [2,30,36]. A similar observation was seen in AM and all the species of Ficus due to waxy-glabrous leaf.…”
Section: Dac and Aptisupporting
confidence: 65%
“…The capacity of plants to check air pollution is well recognized and cited in the standard literature on numerous occasions [2][3][4][5]. Foliar uptake [5][6][7] of metal and metalloid particulates is reported by many authors [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Both ivy and strawberry leaves are considered to be hydrophilic (Walker et al, 2015). Yet, we hypothesize that strawberry leaves are less hydrophilic than ivy leaves (Figures S.2, S.3), which may prevent the deposition of particles (Bakker et al, 1999;Barima et al, 2016). A wind tunnel experiment also showed that the permeability of strawberry leaves, i.e.…”
Section: Leaf-surface Particle Depositionmentioning
confidence: 91%
“…El PM, especialmente la fracción fina, a menudo contienen hidrocarburos aromáticos policíclicos, dibenzo-p-dioxinas policloradas y dibenzofuranos, bifenilos policlorados y metales pesados (Barima et al, 2016). Las partículas finas y ultrafinas generalmente se originan en procesos de combustión, como el escape de un motor o incendios forestales, y consisten en compuestos carbonosos y metales de transición como vanadio (V), Ni y Zn.…”
Section: Composición Químicaunclassified